Traumatic Inferior Shoulder Dislocation with Posterior Cord Brachial Plexopathy: A Case Report - Robert Hall III; Ankur Narain; Lydia Parzych (Journal of Orthopaedic Case Reports)
Introduction: Inferior glenohumeral dislocations are rare injuries, comprising <1% of shoulder dislocations. While their presentation is rare, these injuries commonly result in associated bony injuries, neuropraxia, and tendon injuries. Proper management of such injuries typically requires advanced imaging and consultation with multiple specialists. Here, we present the unique case of inferior glenohumeral dislocation and resultant brachial plexopathy in a patient with previous rotator cuff repair that required subsequent operative management for delayed sequelae of his injury. Interestingly, initial magnetic resonance imaging (MRI) demonstrated the integrity of the prior repair, and there was no clinically significant rotator cuff pathology acutely following the injury. Given the persistent weakness in external reduction and abduction, a repeat MRI was obtained, demonstrating rotator cuff tearing and requiring operative management. Excellent outcome was achieved at 1 year. Case Report: A 62-year-old male with a history of rotator cuff repair presented with inferior glenohumeral dislocation and posterior cord brachial plexopathy after a bicycle accident. Closed reduction was performed. Acute MRI demonstrated intact rotator cuff repair. Repeat MRI demonstrated rotator cuff injury, which required late operative intervention. Electromyography and clinical examination 1 year following his injury demonstrated continued improvement in his posterior cord plexopathy with complete resolution of pain and ability to return to work and perform activities of daily living as assessed by American Shoulder and Elbow Surgeons score. Conclusion: Inferior shoulder dislocations are rare injuries that may be associated with bony injuries, neuropraxia, and tendon injuries. These associated complications can result in delayed presentation of rotator cuff pathology, particularly in the setting of prior rotator cuff repair. Recovery of the neuropraxia can be expected but frequently requires specialist evaluation and invasive testing. Despite its delayed presentation, repair of the rotator cuff tendon paired with trapezius transfer and neurolysis resulted in an excellent outcome.